Using contemporary psychological perspectives to intensify the involvement of psychologists in Philippine schools - Bernardo, Allan B. I. (Philippine Journal of Psychology, 1996)
This paper presents arguments for intensifying the involvement of psychologists in schools, particularly for the restoration of the psychologist's function of studying the learning process and and for the greater integration and application of contemporary perspectives on learning to different components of the learning process. The paper first traces a brief history of the role of psychological theories of learning and intellectual performance in education. The most critical elements in the emerging theories of human learning and their implications for the various functions and elements of schools are then discussed. In particular, the paper describes how recent psychological research and theory give rise to new perspectives on (1) the characteristics of effective learning processes in the student, (2) the nature of knowledge, and (3) the role of the teacher. From the discussion of this perspective, the paper discusses concrete ways by which psychologists can contribute to the central training functions of schools and, more importantly, to guide the movement toward meaningful educational reform. In particular, the paper describes how psychologists can help in (1) teacher training, (2) designing learning environments, and (3) evaluating educational programs.